Interaction monitoring model of logo counseling website for college students’ healthy self-esteem - Jacob Daan Engel; Ventje Jeremias Lewi Engel; Evangs Mailoa (International Journal of Evaluation and Research in Education (IJERE), 2020)
The purpose of this research is to develop the client-counselor interaction monitoring model of the logo counseling website. The model attempts to help counselors in guiding and helping the students (clients) to achieve healthy self-esteem. Machine learning techniques integrated into the model will ensure that the recommendations can be available for counselors and supervisors in the near real-time environment. For the first implementation, a chatbot application is developed and tested with excellent responses from the students. Further research is needed to implement the complete specifications of the interaction monitoring model on the logo counseling website.